2007
DOI: 10.1109/tpwrs.2007.894858
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Bilateral Contracts in Electricity Markets

Abstract: The use of Decision Support Systems (DSS) in the field of Electricity Markets (EM) is essential to provide strategic support to its players. EM are constantly changing, dynamic environments, with many entities which give them a particularly complex nature. There are several simulators for this purpose, including Bilateral Contracting. However, a gap is noticeable in the pre-negotiation phase of energy transactions, particularly in gathering information on opposing negotiators. This paper presents an overview o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 28 publications
0
39
0
1
Order By: Relevance
“…The findings in Table III reveal that, for each given risk aversion level A G for G6, a higher risk aversion level A L for LSE 2 results not only in a higher S but also in an M that 5 As required by Theorem 2, it can be shown that the setting S R = 15 is smaller than S R * in (27) and the setting S U = 25 is greater than…”
Section: B Findings 1) Risk-aversionmentioning
confidence: 89%
See 1 more Smart Citation
“…The findings in Table III reveal that, for each given risk aversion level A G for G6, a higher risk aversion level A L for LSE 2 results not only in a higher S but also in an M that 5 As required by Theorem 2, it can be shown that the setting S R = 15 is smaller than S R * in (27) and the setting S U = 25 is greater than…”
Section: B Findings 1) Risk-aversionmentioning
confidence: 89%
“…Khatib and Galiana [5] propose a practical process in which the bargainers take both benefits and risks into account. They claim that their proposed process will lead to agreement on a mutually beneficial and risk-tolerable forward bilateral contract.…”
mentioning
confidence: 99%
“…Set of constraints (22) is related to the initial status of the units. The constant L i represents the number of initial periods during which unit i must be online.…”
Section: Minimum Up Time and Minimum Down Timementioning
confidence: 99%
“…En este trabajo se utilizan los mismos criterios de la teoría clásica de valoración de portafolio, aproximación media-varianza, mediante investigación la consideración de portafolios de comercialización que incluyen una defi nición de activo libre de riesgo, correspondiente a la utilización de contratos y activos riesgosos, representados por los precios spot en diferentes zonas. Khatib y Galiana [7] proponen un esquema de negociación dinámico en el cual la interacción de la compañía de generación en cada mercado se va ajustando de acuerdo con el comportamiento de los precios spot y forward de la electricidad. Este modelo contempla la posibilidad de que la compañía de generación cumpla sus contratos de ventas a partir de la compra de energía en el mercado spot cuando le conviene.…”
Section: Introductionunclassified